DESIGN AND PRELIMINARY STUDY OF SUBSURFACE DRAINAGE IN HAMBALANG COMPLEX BOGOR - Rokhmat Hidayat; Samuel Jonson Sutanto; Santosa Sandy Putra (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
The Pusat Pendidikan Pelatihan dan Sekolah Olah Raga Nasional (P3SON) construction project was conducted at Hambalang, Sentul, Bogor, West Java. The project area covers 32 hektares. The P3SON project is located at a small mountain, called Gunung Hambalang, which has steep slope and thick clay layer. Generally, Hambalang morphology has a slope of about 1045, and at some places the buildings are built on steep slopes with the degree of steepness more than 45. Based on to the bore log, the rock profile is silt rock with the deepness of 0-6 m, and under 6 m, there is a hard clay layer. Clay layer if it is in contact with water will become impermeable and thus swell. During the high intensity rainfall event, the landslide risk is high. In order to strengthen the slope stability, an outer subsurface drainage at the East side and also horizontal subsurface drainage system in the area itself are proposed. The twin iron pipes are designed for the East side drainage system with the diameter of 20-35 cm and laid 5 m under the surface elevation. Technically, there are fifteen locations that need horizontal drainage installation. Horizontal drainage pipes are designed with 10 cm diameter and 8 m interval between pipes. The length of the horizontal drainage pipes is 15-20 m with slope of 10. Due to the fact that the silt layer depth is 0-6 m, then the horizontal drainage pipes will be located in 3-5 m depth from the surface. Optimistically, this system will reduce the landslide risk in Hambalang area.